Feminists and queer theorists debate the future of critical management studies - Linstead, Alison, 1971-; Harding, Nancy, 1952-; Phillips, Mary, 1955- (Emerald Publishing Limited, 2017)
'What is CMS for and what might its future be- both inside the domain of academia and outside it? It's a question that has beguiled and frustrated academics within and outside its community. At the hear of CMS is an enduring skepticism concerning the social and ecological sustainability of prevailing ideas and forms of management and organization. Using ideas from feminist and queer theory, authors of this volume aim to generate some thinking and possibly a nascent agenda. It focuses on the future of CMS but also intertwines it with ideas as to how scholarly communities can engage in working lives differently.
Keywords: Business & Economics -- General.; Business competition.; Critical theory.; Queer theory.; Management.; elektronické knihy; electronic books